DETERMINANTS OF THE HIGH FREQUENCY OF CESARIANS AT THE REFERENCE GENERAL HOSPITAL OF BANALIA - Désiré BARUANI KYAGA., (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Reducing maternal and perinatal mortality is a global priority. Faced with the abnormal frequency of caesarean section targeting the survival of the mother and the child as well as the relative mortality observed at the General Reference Hospital of Banalia in the first half of 2018, the aim of this work was to contribute to the reduction of maternal and perinatal mortality.Specifically, this study aimed to highlight the frequency of caesarean sections, the sociodemographic  characteristics of cesarean sections, the indications and the mortality relative to these cesarean deliveries. Finally, the study set out to identify the determinants of the high frequency of cesarean section in this hospital.